Cultura digital e cidadania: dialogando a partir de práticas e do currículo dos anos iniciais em escola participante de um projeto de inclusão digital - Selau, Patrícia Reginalda da Silva (Universidade do Vale do Rio dos Sinos, 2016)
This dissertation is a study that discusses the possible dialogues between digital culture, citizenship and the elementary school curriculum in the in a school participating in a digital inclusion project in the metropolitan region of Porto Alegre - RS. Two questions guided this research: 1) How public policies, projects, actions that deal with citizenship theme associated with the perspective of digital inclusion are linked? 2) What are the possibilities of dialogue between the curriculum of the initial years and the issues related to citizenship? It was developed in the school context, a workshop with the theme: digital citizenship and media. Which aimed to discuss the development of citizenship mediated by digital technologies already present in the school context. To cope with the demands and issues that emerged by the acquaintanceship at school, the research and analysis methodology were inspired by the cartographic method of research and based on the ideas of Moreira and Candau (2006) about curriculum, Gadotti (2000) about citizenship and Maraschin and Axt (2005) about technological engagement, it was found that both the concept of curriculum and the concept of citizenship are large and complex concepts that allow various interpretations, And realize that the TD present in the school are treated as a pedagogical tool, as a support to the teaching process, and not as a cultural artifact conducive to the development of citizenship. Citizenship was not perceived in the context of research as active and purposeful participation of citizens. According to recurrences in the discourses of teachers, the internet searches were the most common form of use of the TD in the context of school, however, this recurrence in the process does not constitute a technological engagement. It was observed appropriation of participants in relation to concepts problematized in the course of this research, generating movements and possible innovations in some practices evidenced in the course of this investigation.
Keywords: Digital; Tecnologias digitais; Currículo; Cidadania; Inclusão digital; Digital culture; Digital technologies; Curriculum; Citizenship; Digital inclusion; ACCNPQ::Ciências Humanas::Educação